"Ah … the power of mothers": Bereaved mothers as victim-heroes in media enacted crusades for justice. (December 2016) - Wright, Sarah
The display of maternal suffering is powerful, as the bereaved mother's experience represents any parent's deepest fear. When her pain is enmeshed with calls to support changes in our justice systems, it has the potential to bring about unconstitutional effects, for a mother's love has no end and so her life sentence can only be addressed with equal amounts of endless suffering for the said offender (Valier and Lippens, 2004). This paper explores the construction of the bereaved mother figure as a victim-hero within contemporary media enacted crime narratives. It examines two murder cases in the New Zealand context where a bereaved mother's displays of grief can be linked to changes made to the legal code. It will be argued that the character of the bereaved mother as a victim-hero has become a powerful agent of change that has implications for criminal justice system modification. It is argued that critical attention is required of criminology to the role of the good mother in criminal justice discourses, and in particular to the ways in which the good mother is characterised in mediated public discourses.